Relationship Between Plasma Acid Sphingomyelinase and Alteration in Taste and Smell as Indicator of Long COVID in Pregnant Women - Federico Fiorani; Giulia Moretti; Laura Cerquiglini; Chiara Gizzi; Giulia Gizzi; Paola Signorelli; Samuela Cataldi; Tommaso Beccari; Elisa Delvecchio; Claudia Mazzeschi; Stefania Troiani; Elisabetta Albi (Reports)
Background: Persistent alterations in taste and smell affect a significant proportion of individuals following COVID-19, representing a component of post-acute COVID-19 syndrome, commonly referred to as long COVID. The degradation of sphingomyelin by acid sphingomyelinase is regarded as a biomarker for acquired demyelinating neuropathies. Objectives: This study was aimed to enroll women who contracted COVID-19 during pregnancy and experienced persistent alterations in taste and/or smell for more than 1 year post-infection, in comparison to pregnant women without any disturbances in these senses. Methods: The patients were subjected to a questionnaire investigating smell and taste disorders more than 1 year after the infection. Then, the levels of acid sphingomyelinase in the plasma of the participants were assessed. Results: The results showed that in women who had been pregnant and who had been infected with SARS Cov-2 during the COVID period and who still had taste and smell disorders 1 year later, plasma acid sphingomyelinase levels were double that of pregnant women who had contracted the infection during the COVID period but had not reported taste and smell disorders and that of pregnant women analyzed after the COVID period. Conclusions: The results suggest a hypothesis that the persistence of sensory disturbances in long COVID was probably due to a failure to utilize brain circuitry with demyelination resulting from chemosensory dysfunction of the olfactory epithelium.